Price dividend models, expectations formation, and monetary policy - Nico Valckx (Hamburg Institute of International Economics (HWWA), 2003)
This paper applies the Campbell-Shiller (1988) methodology to estimate a price dividend model with volatility and inflation risk, extending existing models in this field. The model fits the data well over the period 1979-2002 for the Euro Area, but less so for the U.S. The latter is interpreted as reflecting fads and is borne out by a decomposition of the price dividend ratio into a fundamental and bubble part. Finally, it is shown that deviations from fundamentals enter significantly in the Fed's interest rate reaction function but at the cost of destabilising monetary policy. Alternatively, in case that Fed policy remained stable, there was not much of attention to asset bubbles. For the Euro Area, historically, the reaction function does not appear to react much to asset prices.
Keywords: E44; G12; 330; dividend price ratio; dynamic Gordon model; asset price bubbles; Taylor rule; Kapitalertrag; Börsenkurs; Bubbles; Wertpapieranalyse; Volatilität; Inflationserwartung; Capital Asset Pricing Model; Geldpolitik; Schätzung; Vereinigte Staaten; EU-Staaten